Implikasi Kurikulum Merdeka Pada Pengembangan Instrumen Penilaian Hasil Belajar PAI - Warsiyah, Warsiyah; Athoillah, Sukijan; Soqiluqi, Ahmad (Universitas Wahid Hasyim Semarang, 2023)
The government's policy to change Curriculum 13 to an independent learning curriculum has an effect on changing paradigms and learning objectives in general, including Islamic learning. The measure of success between students cannot be equated but instead must be independent in accordance with the independent learning curriculum concept. it is important for teachers who teach PAI subjects to be able to develop learning evaluations according to the principles and objectives of the independent learning curriculum. This study aims to analyze the challenges and opportunities of Islamic Religious Education teachers in developing Islamic Education learning instruments in the Freedom to Learn era. The results of the study show that there are implications for the independent curriculum for student assessment, namely the teacher must develop the three types of instruments needed, namely at the beginning of learning, during learning and at the end of learning. The types of assessment instruments developed at the beginning of learning can be in the form of written tests in the form of descriptions, multiple choice and checklists. Assessment instruments during learning are in the form of observation, oral and performance, while instruments for final assessment of learning can be in the form of multiple choices, descriptions and oral tests.